Evaluation of the total contents and bioaccessible fractions of inorganic constituents in nutritive flours exposed to consumption in Brazil - Thaís Luz de Souza; Leilane Rodrigues Santos; Caio Silva Assis Felix; Laura Beatriz Souza e Souza; Ivana Ferreira Simões; Crislaine Santos Lima; Marcele Catarino Souza dos Santos; Rennan Geovanny Oliveira Araújo; Aníbal de Freitas Santos Júnior; Daniele Cristina Muniz Batista Santos (Journal of Trace Elements and Minerals, 2025)
Introduction: Inorganic constituents are chemical elements or metal ions essential for human survival, through regulatory mechanisms in various cellular processes. The aim of this study was to determine the total (TT) and bioaccessible (TB) content of inorganic constituents in 20 nutritive flour (NF) samples exposed to consumption in Brazil, using the INFOGEST in vitro digestion method. Methods: Approximately 0.250 g of NF sample was digested in a closed digestion block with 2.8 mL of 65 %(m m-1) HNO3 + 1.0 mL of 30 %(m m-1) H2O2 + 4.2 mL of deionized water, for 45 min at 200 °C. Concentrations of Al, Ba, Ca, Cu, Fe, K, Mg, Mn, Na, P, Sr and Zn were determined by inductively coupled plasma optical emission spectrometry (ICP OES). Estimates of the bioaccessible levels of microelements (Al, Cu, Fe, Mn, and Zn) were performed based on the in vitro INFOGEST protocol. Results and Discussion: The range of total microelement contents in the NF (dry weight, in µg g-1) were: Al (18.00 to 333), Ba (0.98 to 67.10), Cu (1.45 to 75.51), Fe (8.57 to 337), Mn (0.38 to 107), Sr (0.54 to 59.39), and Zn (3.44 to 122). Macroelement contents (dry weight, in µg g-1) were: Ca (43.12 to 5276), K (71.60 to 11,392), Mg (42.09 to 6519), Na (63.85 to 1668), and P (134 to 19,359). Significant concentrations of Fe, Mg, Mn, P and Zn were found in pumpkin seed flour. Copper levels in grape seed flour was high when compared to the other samples analyzed. Multivariate analysis showed groupings and similarities among the samples. Bioaccessible contents (in %) ranged from Al (0.21 to 10.37), Cu (2.93 to 26.57), Fe (1.39 to 36.46), Mn (0.73 to 107), and Zn (3.71 to 117). In the NF analyzed, Mn and Zn were the elements most available in the gastrointestinal fluids. Conclusion: The technique of ICP OES proved to be adequate, as it showed good linearity, sensitivity, precision and accuracy for the determination of inorganic constituents in NF samples. Variations in inorganic composition between NF were observed. This study contributes to the expansion of the contribution of NF to the diet of the population.